2019
DOI: 10.1002/lary.27760
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and pharmacokinetic analysis of oxymetazoline use during nasal surgery in children

Abstract: Objectives/Hypothesis: Oxymetazoline is an α-adrenergic agonist that is commonly used as a topical hemostatic agent in the operating room during ear, nose, and throat surgery. There are limited data on oxymetazoline pharmacokinetics in children who undergo general anesthesia. We assessed the hemodynamic effects and systemic absorption of topically applied oxymetazoline in children undergoing various nasal procedures. Study Design: Prospective trial. Methods: Children ages 2 to 17 years undergoing functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Delivery can be achieved through the use of microbrush (~0.015 mL of solution) or defined volume soaking of small cotton balls (1 drop~0.05 mL) common in primary tooth pulpotomy procedures. As stated previously defined volume soaked pledgets on nasal mucosa had minimal systemic effects in children and it is postulated that there is a self-limiting bioavailability of oxymetazoline through local vasoconstriction [ 1 , 27 ]. This concept can be applied to pulpal tissue, where near immediate hemostasis of the small pulp exposure will limit systemic absorption of the ImD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Delivery can be achieved through the use of microbrush (~0.015 mL of solution) or defined volume soaking of small cotton balls (1 drop~0.05 mL) common in primary tooth pulpotomy procedures. As stated previously defined volume soaked pledgets on nasal mucosa had minimal systemic effects in children and it is postulated that there is a self-limiting bioavailability of oxymetazoline through local vasoconstriction [ 1 , 27 ]. This concept can be applied to pulpal tissue, where near immediate hemostasis of the small pulp exposure will limit systemic absorption of the ImD.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this review is to formulate a conceptual model on the potential management of pulpal tissue by imidazoline derivatives (ImDs) based on a review of the literature that examines the hemostatic properties and mechanistic actions of these compounds in other human tissues. Commercial ImDs are formulated in solution with antimicrobial preservatives in order to act as ‘parenteral topical agents’ and used to manage ophthalmic inflammation, nasal congestion, and to control bleeding during otolaryngology surgery [ 1 , 2 ]. While systematic reviews of IMDs in medicine are published [ 3 , 4 , 5 ] this critical review proposes an advancement in dental pulpal management by examining the pharmacology and biochemistry of ImDs, which have been largely understudied for direct dental application [ 6 , 7 , 8 , 9 ].…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Thank you for your comments regarding our article "Hemodynamic and Pharmacokinetic Analysis of Oxymetazoline Use During Nasal Surgery in Children". 1 The authors are grateful that you found our study informative, as your work has been the motivation for our interest in this subject. 2 Currently, the United States Food and Drug Administration (FDA) approves oxymetazoline use in patients who are ≥6 years of age.…”
mentioning
confidence: 83%